2010
DOI: 10.1525/mp.2010.27.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Humans Rapidly Learn Grammatical Structure in a New Musical Scale

Abstract: Knowledge of musical rules and structures has been reliably demonstrated in humans of different ages, cultures, and levels of music training, and has been linked to our musical preferences. However, how humans acquire knowledge of and develop preferences for music remains unknown. The present study shows that humans rapidly develop knowledge and preferences when given limited exposure to a new musical system. Using a non-traditional, unfamiliar musical scale (Bohlen-Pierce scale), we created finite-state music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
235
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(259 citation statements)
references
References 42 publications
22
235
2
Order By: Relevance
“…However, careful examination of the existing research shows that all encultured listeners perceive music remarkably similarly (Bigand & Poulin-Charronnat, 2006 ). With a specific view towards abstract organizational structures, both musically trained and untrained listeners show the same patterns of perception of tonality (Hébert, Peretz, & Gagnon, 1995;Koelsch, Gunter, Friederici, & Schröger, 2000;Loui, Wessel, & Kam, 2010;Tillmann & PoulinCharronnat, 2010;Trainor & Trehub, 1994;van Egmond & Boswijk, 2007) and meter (Geiser, Ziegler, Jancke, & Meyer, 2009;Hannon et al, 2004). The present studies extend these general findings by revealing that musical training is not associated with any qualitative differences in pitch-time integration.…”
Section: ---Insert Figure 4 About Here----discussionsupporting
confidence: 74%
“…However, careful examination of the existing research shows that all encultured listeners perceive music remarkably similarly (Bigand & Poulin-Charronnat, 2006 ). With a specific view towards abstract organizational structures, both musically trained and untrained listeners show the same patterns of perception of tonality (Hébert, Peretz, & Gagnon, 1995;Koelsch, Gunter, Friederici, & Schröger, 2000;Loui, Wessel, & Kam, 2010;Tillmann & PoulinCharronnat, 2010;Trainor & Trehub, 1994;van Egmond & Boswijk, 2007) and meter (Geiser, Ziegler, Jancke, & Meyer, 2009;Hannon et al, 2004). The present studies extend these general findings by revealing that musical training is not associated with any qualitative differences in pitch-time integration.…”
Section: ---Insert Figure 4 About Here----discussionsupporting
confidence: 74%
“…Similarly, relative to non-musicians, musicians have larger P2 amplitudes to novel sung melodies they have not previously heard versus familiar sung melodies heard during an exposure phase (Francois and Schön, 2011). In contrast, Rohrmeier et al (2011) found no difference between musicians and non-musicians on a sequence familiarity judgement task, after passive exposure to tone sequences built from a finite state grammar (see also Loui et al, 2010).…”
Section: Auditory Scene Analysismentioning
confidence: 96%
“…Shook et al, 2013; see also Reber, 1993, for discussion). As suggested by Loui et al (2010) detailed (and likely explicit -see Hannon & Trainor, 2007) knowledge of Western tonal relations may therefore have interfered with learning or using the familiarized statistical regularities within our tone sequences (Loui et al, 2010;McMullen Jonaitis & Saffran, 2009). This suggests that learning of novel, regular auditory structures may be limited by prior expert knowledge or expectations.…”
Section: Sequence Perception and Reproductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accounting for tonal influences would offer a particularly interesting avenue for future work in this area. Indeed, use of equidistant pitches from an unfamiliar scale, such as the Bohlen-Pierce Scale (Loui et al, 2010), could potentially eliminate such influences from long-term exposure.…”
mentioning
confidence: 99%